2022
DOI: 10.1159/000522158
|View full text |Cite
|
Sign up to set email alerts
|

A Descriptive Evaluation of Health Literacy and Determinants of COVID-19 Vaccine Acceptance among Patients with IgA Nephropathy with High Vaccine Uptake

Abstract: Aims: Shared decision-making regarding COVID-19 vaccination in IgA nephropathy involves the ability to handle health information regarding potential benefits and risk of flare, but few studies have evaluated health literacy in the context of vaccination. We aimed to evaluate the health literacy and COVID-19 vaccination uptake and acceptance in IgA nephropathy. Methods: Single-center cross-sectional study of 126 consecutive patients with IgA nephropathy. Health literacy was assessed using the HLS-EU-47 question… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 24 publications
(31 reference statements)
0
2
0
Order By: Relevance
“…The study showed that younger participants <50 years old and those who spoke English at home had significantly higher general HL with 85.4% of participants finding it very easy to find information on vaccinations and understand the need for vaccinations. 49 Research in Turkey revealed that the HL scale total score mean was 54.92 ± 23.64 and from them 56.4% received the COVID-19 vaccine. The total mean scores from the HL scale were found to be significantly higher among civil servants ( p < 0.05).…”
Section: Resultsmentioning
confidence: 99%
“…The study showed that younger participants <50 years old and those who spoke English at home had significantly higher general HL with 85.4% of participants finding it very easy to find information on vaccinations and understand the need for vaccinations. 49 Research in Turkey revealed that the HL scale total score mean was 54.92 ± 23.64 and from them 56.4% received the COVID-19 vaccine. The total mean scores from the HL scale were found to be significantly higher among civil servants ( p < 0.05).…”
Section: Resultsmentioning
confidence: 99%
“…Patients at the Glomerulonephritis Clinic were offered the self‐administered survey, 5 while patients with glomerulonephritis due to IgA nephropathy were invited to participate in an interviewer‐administered telephone questionnaire. 6 Awareness of the influenza vaccine and determinants of vaccine acceptance were adapted from the World Health Organization framework. 7 Ninety patients with glomerulonephritis participated in the survey (response rate 60%).…”
mentioning
confidence: 99%